Coordination and Governance among Tour Agencies and Tourist Attractions: An Analysis of Tourism Production Systems in Brazil - Arruda, Dyego de Oliveira; Mariani, Milton Augusto Pasquotto; de Carvalho, Dirceu Tornavoi (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2016)
The successful planning and development of tourism requires systemic coordination and participation of agents from various economic sectors. This study analyzes the coordination and governance among tourist attractions and tour agencies in the city of Bonito, State of Mato Grosso do Sul, Brazil, a leading ecotourism destination in that country. Transaction cost economic theoretical framework is used in this paper, taking transactions as the unit of analysis. Four tour agencies, three tourist attractions managers, and five representatives of institutional environment were surveyed in the city of Bonito. A semi-structured questionnaire was administered to tour agencies and tourist attractions managers, and personal interviews were conducted with institutional and organizational agents. Research results suggest predominance of hybrid forms of governance among tour agencies and tourist attractions. Moreover, the institutional environment in the analyzed tourism system is highly significant with respect to the coordination and structural configuration of the tourism system, minimizing potential uncertainties and opportunistic behavior of agents in the analyzed tourism system. Keywords: Tourism. Governance Structure. Tourism Production Systems. Bonito, MS, Brazil Coordenação e Governança entre Agências de Turismo e Atrações Turísticas: Uma análise de Turismo Sistemas de Produção no Brasil - O sucesso do planejamento e o desenvolvimento do Turismo requerem uma coordenação sistêmica e a participação dos agentes de vários setores econômicos. Este estudo analisa a coordenação e governança entre as atrações turísticas e agências de turismo da cidade de Bonito, Estado de Mato Grosso do Sul, Brasil, um destino de ecoturismo líder no país. É usado um quadro teórico [framework ] custo de transação econômica, tendo como unidade de análise as transações. Foram pesquisados, ??na cidade de Bonito, quatro agências de turismo, três gerentes de atrações turísticas e cinco representantes do ambiente institucional. Um questionário semiestruturado foi aplicado nas agências de turismo e com os gestores de atrações turísticas, e entrevistas pessoais foram realizadas com agentes institucionais e organizacionais. Os resultados da pesquisa sugerem predominância de formas híbridas de governança entre agências de turismo e atrações turísticas. Além disso, o ambiente institucional analisado é altamente significativo no que diz respeito à coordenação e configuração estrutural do sistema de turismo, minimizando potenciais incertezas e comportamento oportunista dos agentes no sistema de turismo analisados. Palavras-chave: Turismo. Estrutura de Governança. Sistema de Produção Turística. Bonito, MS, Brasil. Dyego de Oliveira Arruda - Master. Professor at Federal Center of Technological Education ‘Celso Suckow da Fonseca’, Rio de Janeiro, Brazil. Curriculum: <span style="font-size: 10pt; font-family: Calibri, sans-serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="X-NONE">http://lattes.cnpq.br/5222976964204691<span style="font-size: 10pt; font-family: Calibri, sans-serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">. E-mail: dyego.arruda@gmail.com Milton Augusto Pasquotto Mariani - Doctor. Professor at School of Management and Business in the Federal University of Mato Grosso do Sul, Campo Grande, Mato Grosso do Sul, Brazil. Curriculum: <span style="font-size: 10pt; font-family: Calibri, sans-serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="X-NONE">http://lattes.cnpq.br/0935409945176042<span style="font-size: 10pt; font-family: Calibri, sans-serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">. E-mail: miltmari@terra.com.br Dirceu Tornavoi de Carvalho – Doctor. Professor in the School of Economics, Business, and Accounting at the University of São Paulo, Ribeirão Preto, São Paulo, Brazil. Curriculum:<span style="font-size: 10pt; line-height: 115%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"> <span style="font-size: 10pt; line-height: 115%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"> <span style="font-size: 10pt; line-height: 115%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">http://lattes.cnpq.br/8239366580041946. E-mail: dirceutornavoi@gmail.com